Pendidikan Karakter Siswa Berbasis Agama di SMP Walisongo Pecangaan Jepara - Subaidi, Subaidi (J-MPI (Jurnal Manajemen Pendidikan Islam), 2019)
This research explain about education character of students based on religion at junior high school of walisongo pecangaan jepara in central java.The research used descriptive qualitative approach. The purpose of research was to know an event at junior high school of walisongo pecangaan jepara in central java in the context of education character of students based on religion.The collection of data via observation, the objective of the interview and documentation. The data analysis used data on non statistics. Our research findings: first, the value of tolerance attitude to the religious, even all she great political pressure to implement values students based character of religions such as; istighoasah-mujahadah, the dhuha pray at the decline fixed ostentatiously and began to pray, the pray dzuhur together; second, the value of care about the environment , this means that , of students in their backs on this and move to action always tried to prevent that damage the natural environment in and around this area, and develop efforts to fix of the nature of those which have occurred; reports of damage or injuries; Third, value tawadhu, it means, students show humility to something exalted; fourth, value respectful deference, it means , a gesture of respect to parents occurred in pay attention and affection, muslims and obey when ruled, keep spoken in talks, do not denied, and demonstrate the attitude of polite when there is behind him; fifth, value discipline, it means, the act of students indicate which behaviors orderly and adherent to various provisions and regulations in their surroundings; those six, value honest, all students to make himself as a man who can diprcaya in run all regulation specified; seventh , value socially responsible, it means, students be and act have always wanted to provided assistance in others and poor people; eighth , value spirit nationality, it means, a way of thinking, act and insightful who puts the national interest and country.